Ear diseases pattern and hearing impairment in the Eastern Nepal- A study in a combined eye and ear set up - Thakur, Sanjeev Kumar; Singh, Sanjay Kumar; Mahato, Bindeshwar; Singh, Anand (Asian Journal of Medical Sciences, 2015)
Background: This is a prevalence study of ear diseases and hearing impairment done in acombined eye and ear set up of Biratnagar Eye Hospital. This study was conducted in theSunsari and Morang districts of Nepal. Its aim is to fi nd out the ear disease and hearingimpairment prevalent in the community. Materials and Methods: A total of 2259 people who visited eyecamps were screened for ear diseases. Patients were examined by the eye and ear assistantsunder supervision of otolaryngologist. A head mirror, an otoscope, an aural syringe, kidneytrays and light source and a set of tuning forks (512 and 256 Hz) were used to assessthe ear diseases and hearing loss. Results: A total of 1094 patients presented with eardiseases. Males were more than females [608(55.42%) vs. 486(44.57%)]. Children up toand below 15 years were 386 (35.28%). The frequency of ear diseases were as follows:Impacted wax- 319 (29.15%), chronic suppurative otitis media mucosal type - 307(28.06%),otomycosis - 66 (6.03%), furunculosis/otitis externa - 46 (4.29%), Acute suppurative otitismedia - 46 (4.2%), tubal catarrhal - 34(3.1%), otitis media with effusion - 24 (2.19%),perichondritis - 21(1.91%), Unsafe otitis media - 14(1.27%), Foreign body in theear - 4 (0.36%) cases, Postraumatic perforation of tympanic membrane - 2 (0.18%), deafand mute - 12 (1.09%). presbyacusis and other sensorineural hearing loss- 199(18.19%).The point prevalence of otitis media was 17.3% (391) people. Hearing impairment was64.99 %(635 out of 977 patients above 5 years). Conclusion: Ear diseases and hearingimpairment are very common in Sunsari and Morang districts of Nepal demanding immediatetreatment. DOI: http://dx.doi.org/10.3126/ajms.v6i5.11621 Asian Journal of Medical Sciences Vol.6(5) 2015 51-55